Impact evaluation of EU subsidies for economic development on the Hungarian SME sector - Ádám Banai; Péter Lang; Gábor Nagy; Martin Stancsics (Magyar Nemzeti Bank, 2017)
Although EU funds play a pivotal role not only for Hungary but for the entire European Union as well, there is debate regarding their effectiveness in the literature. This paper investigates the impact of direct economic development subsidies extended in the context of the Cohesion Policy programmes as part of the 2007-2013 programming period of the European Union, on Hungarian micro, small and medium-sized enterprises. Based on a micro database, we assess the effects of the beneficiaries' first subsidies on various performance indicators, using a combination of propensity score matching and fixed effects panel regression. According to our results, economic development funds had a significant positive impact on the number of employees, sales revenue, gross value added and in some cases, operating profit. However, the labour productivity of beneficiaries was not significantly affected by any of the support schemes. Furthermore, by explicitly comparing non-refundable subsidies (grants) and refundable assistance (financial instruments) extended under the Structural Funds and the Cohesion Fund, we find that there is no significant difference in their effectiveness.
Keywords: D04; G38; H25; O22; 330; programme evaluation; EU subsidies; firm-level effects; propensity score matching; fixed effects